(untitled) (Journal of University of Babylon for Engineering Sciences, 2023)
The goal of this study is to use friction stir welding to improve the welding zone of Low-Density Polyethylene sheets by adding alumina powder with a particle size of 25 . Welding was done with a shoe tool at a zero-tilt angle, with alumina powder percentages of 10, 15, 20, 25, and 30 % added to the welding zone. In all welding experiments, the same 520 rpm tool rotational speed and 20 mm/min tool travel speed were applied. In all instances of the additional percentages of alumina powder, mechanical testing like tensile, flexural, and hardness tests revealed that the welded specimens’ mechanical characteristics were better than those of the base substance. The friction stir welding technique increased the mechanical properties, formed defect-free joints, and created excellent low-density polyethylene sheet weldments that were reinforced with alumina powder according to the test results. The best results for mechanical properties were achieved by adding 10% of alumina powder to the welding zone.